INTERAKSI SIMBOLIK TRADISI GUMBREGAN SEBAGAI MEDIA TRADISIONAL DI ERA MODERN BAGI MASYARAKAT DESA TUNGGUNJAGIR KECAMATAN MANTUP KABUPATEN LAMONGAN - Sutrisno; Awang Dharmawan (The Commercium, 2025)
Gumbregan is a tradition carried out in Tunggunjagir Village, Mantup District, Lamongan Regency. The gumbregan tradition is an expression of people's gratitude for the good fortune that has been given by Almighty God. The gumbregan tradition is a community ritual communication medium in preserving traditional culture that still survives in today's modern era. The aim of this research is to determine the symbolic interactions of the gumbregan tradition as a communication medium for the people of Tunggunjagir village. The Symbolic interaction theory approach, namely mind, self and society by George Herbet Mead was used to find the results of social phenomena that occurred in the Gumbregan tradition of the people of Tungungnjagir Village. This research is qualitative research with a case study method. Data was obtained from observations and in-depth interviews with informants. The results of this research produce (1) Mind, the people of Tungungnjagir Village think that the gumbregan tradition is a medium for community ritual communication. This communication is realized in the form of an expression of gratitude to God Almighty. (2) Self, people's view of themselves and the Gumbregan tradition contains motifs of artifacts, social existence, ideas of mutual cooperation and the formation of ideology and cultural values in society. (3) Society, In this concept, the gumbregan tradition is a projection of society's hopes for being able to raise livestock. Apart from that, there is also the influence of the Opinion Leader in implementing this tradition, namely as a provider of information and outreach to the public to follow this tradition. Keywords: Symbolic Interaction, Indonesian Communication System, Rural Communication, Gumbregan, Tunggunjagir Village